Intra-session reliability of isometric muscle strength of the bilateral standing press in female handball players - Cifuentes-Zapata, Claudio; Andrades-Ramírez, Oscar; Ulloa-Díaz, David; Rodríguez-Perea, Ángela; Huerta Ojeda, Álvaro; Chirosa-Ríos, Luis Javier (PeerJ, 2024)
Background Systematizing reliable protocols and procedures for strength assessment in handball has allowed for a more thorough kinetic analysis and increased precision in detecting training-induced changes in muscular strength. The evaluation of upper limb strength with a bilateral standing press (BSP) exercise in handball players approximates blocking actions in the defensive phase, pushing and fixation. Aim The aim of this study was to analyze the relative and absolute reliability of intra-session comparisons in an isometric peak muscle strength protocol in a bilateral standing press (BSP) exercise among female handball players. Methods Sixteen young female handball players at an international level, aged between 22 ± 4 years, with no prior experience in using functional electromechanical dynamometers (FEMD) participated in this study. The participants initiated the assessment of maximum isometric force in a bipedal stance with a forward projection of the dominant foot between 20 and 30 cm. The knees were kept semi-flexed, and the hip extension of the non-dominant limb ranged from 15 to 20°. Bilateral anterior push of the upper limb was performed with shoulder abduction and elbow flexion at 90°, maintaining a pronated hand position. Participants were instructed to exert three sets of maximal force for 5 s in BSP exercise. Relative reliability was assessed using the model intraclass correlation (ICC) and absolute reliability was assessed using the coefficient of variation (CV) and standard error of measurement (SEM). For this study, the parameters of maximum and mean muscle strength were considered. Results The results demonstrated high relative reliability (ICC 0.93–0.97) and absolute reliability (SEM 0.19–2.79) y (CV 4.78–9.03) for both mean force and peak force, with no significant differences between the sets (p > 0.05), indicating a negligible effect size (0.01−0.12). Conclusion The mean and peak isometric muscle strength for the BSP exercise controlled with FEMD in female handball players exhibits high relative and absolute reliability between series.
Keywords: Muscle strength; Dynamometer; Isokinetic; Sports; Reliability